Prevalence and molecular epidemiology of bovine leukemia virus in Colombian cattle (2020)
Bovine leukemia virus (BLV) is one of the five agents considered most significant for cattle. It is important to determine the prevalence and molecular epidemiology of BLV throughout the country in order to gain a more thorough understanding of the current situation of BLV and to reveal the possibility of masked genotypes that the primers used by OIE are unable to identify. Blood samples were collected at random from 289 cows distributed in 75 farms across the country. PCR amplification of env, gag and tax gene segments was performed. The obtained amplicons were sequenced and then subjected to phylogenetic analyses. A total of 62% of the cows present at 92% of the farms were BLV-positive for gag fragment. Genotype 1 was exclusively detected by env gene segment when analyzed using previously reported primers. However, tax gene analysis revealed circulation of genotype 6 variants, which were also detected based on env gene analysis with newly designed primers. These results indicate that current genotyping approaches based on partial env sequencing may bias BLV genetic variability approaches and underestimate the diversity of the detected BLV genotypes. This report is one of the first molecular and epidemiological studies of BLV conducted in Colombia, which contributes to the global epidemiology of the virus; it also highlights the substantial impact of BLV on the country's livestock and thus is a useful resource for farmers and government entities. © 2020 The Authors